Batik Tegalan Sebagai Aset Pendidikan Dan Budaya Masyarakat Tegal - Rosyadi, Imron; Naam, Muh Fakhrihun; Sugiarto, Eko (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Tegal is a coastal region on the north coast of Java. This small region on the west side of Central Java Province has unique characteristics. Like other regions in Java, Tegal has its own distinctive batik-making centers. Almost every region in Indonesia has batik with its own characteristics, such as Solo batik, Pekalongan batik, Banyumas batik, Cirebon batik, Ponorogo batik, Tulungagung batik, Gresik batik, Surabaya batik, Madura batik, and many more with different names. In addition to the batik that has been mentioned, there is also batik that is the pride of the Tegal people, namely Tegalan batik. Batik Tegalan is actually a great potential that Tegal regency has, apart from its tourism sector. Because Tegal batik has a strong competitiveness with other batik. Bright motifs and patterns characterize this batik, which is called coastal batik. But despite its enormous potential, moor batik has not been well known by the people of Tegal in particular, and the people of Indonesia in general. This is due to the lack of promotion, as well as the lack of capital for batik craftsmen who are mostly home industry businesses. In Bengle village, which is known as the batik town of Tegal, almost all of its residents earn a living as batik craftsmen, almost all of them are in the category of SME entrepreneurs.